Early Paracentesis in High-Risk Hospitalized Patients: Time for a New Quality Indicator. (December 2019) - Rosenblatt, Russell; Tafesh, Zaid; Shen, Nicole; Cohen-Mekelburg, Shirley; Kumar, Sonal; Lucero, Catherine; Brown, Robert S.; Verna, Elizabeth; Fortune, Brett; Jesudian, Arun
Abstract : INTRODUCTION: Symptomatic ascites is the most common indication for hospitalization in patients with cirrhosis. Although guidelines recommend paracentesis for all inpatients with ascites, the timing of paracentesis is likely to be crucial. Performance of an early paracentesis and its relationship to outcomes are unknown, particularly among patients at high risk of spontaneous bacterial peritonitis (SBP). METHODS: We included 75, 462 discharges of adult patients with cirrhosis presenting with ascites who underwent paracentesis from the State Inpatient Databases of New York, Florida, and Washington from 2009 to 2013. High-risk patients were identified as having concomitant hepatic encephalopathy or acute kidney injury present on admission. The primary outcome was performance of early paracentesis (within 1 hospital day) with secondary outcomes being inpatient mortality, SBP-related mortality, and 30-day readmission. Multivariable logistic regression models included a priori covariates known to impact outcomes. RESULTS: There were 43, 492 (57.6%) patients who underwent early paracentesis. High-risk patients (27, 496) had lower rates of early paracentesis (52.8% vs 60.5%, P < 0.001). On multivariable analysis, high-risk patients had significantly decreased odds of undergoing early paracentesis (odds ratio [OR] 0.74, 95% confidence interval [CI] 0.71–0.78, P < 0.001). Early paracentesis was associated with a reduced inpatient all-cause mortality (OR 0.68, 95% CI 0.63–0.73, P < 0.001), SBP-related mortality (OR 0.84, 95% CI 0.73–0.94, P = 0.01), and 30-day readmission (OR 0.87, 95% CI 0.82–0.92, P < 0.001). DISCUSSION: Early paracentesis is associated with reduced inpatient mortality, SBP-related mortality, and 30-day readmission. Given its impact on outcomes, early paracentesis should be a new quality metric. Further education and interventions are needed to improve both adherence and outcomes.